PREDIKSI KONDISI FINANCIAL DISTRESS : PERBANDINGAN METODE ALTMAN Z-SCORE DAN ANALISIS DISKRIMINAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Andreas Aji Subagyo, 12.05.52.0090; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2016)
This study aimed to test whether there is a difference the prediction of financial distress between Altman Z-Score method with discriminant analysis of property and real estate companies listed on the Indonesian Stock Exchange. The population in this study are all property and real estate companies listedon the Indonesian Stock Exchange. Which refers to the sample selection purposive sampling method and sample obtained a total of 39 companies. Observation period of 3 (three) years, so that the data obtained is 39 x 3 years of observation, as many as 117 corporatedat, known mostly experiencing financial distress (distress), ie as many as 84 corporate data (71.8%) and 33 corporate data (28.2%) didn’t experience financial distress (non-distress). From the test results can be seen there were no significant differences in the variable Net Working Capital to Total Assets, Retained Earnings to Total Assets and Sales to Total Assets in predicting financial distress. While it is known that the variable Earnings Before Interest and Taxes to Total Assets (EBIT /TA), Market Value of Equity to Book Value of Total Liabilities (MVE / BVTL) showed a significant difference in predicting financial distress. The next results can be seen overall accuracy (Hit Ratio) in the classification based on discriminant analysis that has been done is 94%.Keywords: FinancialDistress, Z-Score, Altman, Discriminant, Property And Real Estate Companies